Evaluation of the YPI Al-‘Arabi online training program in enhancing teachers' pedagogical competence - Nurlatifah Nurlatifah; Laksmi Dewi; Deni Kurniawan (Inovasi Kurikulum, 2025)
The rapid digital development, which not all teachers have fully adapted to, presents challenges in enhancing pedagogical competence. Teachers at YPI Al-'Arabi stated that online training is less effective than offline training, particularly in terms of delivery methods and scheduling. This study aims to evaluate teachers' reactions to the training, its effectiveness in improving pedagogical competence, and the factors that influence it. This research employs a descriptive evaluative method with Kirkpatrick’s model at the reaction and learning levels. The sample consists of 32 teachers selected through purposive sampling. Data were collected using semi-structured questionnaires and pre-test and post-test assessments, with N-Gain analysis to measure knowledge improvement. The findings show that participants' reactions scored an average of 3.37 (84%), with the highest ratings given to instructors. However, the delivery method and schedule require improvement. At the learning level, an N-Gain score indicates moderate effectiveness. Factors influencing training effectiveness include instructional design, material relevance, and limited virtual interaction. In conclusion, this online training has the potential to enhance teachers' competence. However, it requires more innovative approaches. Recommendations include implementing blended learning, improving delivery methods, and adopting more effective interaction strategies.   Abstrak Pesantnya perkembangan digital yang belum sepenuhnya diikuti oleh semua guru menjadi tantangan dalam meningkatkan kompetensi pedagogik. Guru di YPI Al-'Arabi menyatakan bahwa pelatihan online kurang efektif dibandingkan offline, terutama terkait metode penyampaian dan jadwal. Penelitian ini bertujuan untuk menunjukkan tingkat reaksi guru terhadap pelatihan, efektivitasnya dalam meningkatkan kompetensi pedagogik, serta faktor-faktor yang mempengaruhinya. Penelitian ini menggunakan metode deskriptif evaluatif dengan model Kirkpatrick pada tingkat reaksi dan pembelajaran. Sampel terdiri dari 32 guru yang dipilih melalui purposive sampling. Data dikumpulkan melalui kuesioner semi tertutup dan tes pre-test serta post-test, dengan analisis N-Gain untuk mengukur peningkatan pengetahuan. Hasil penelitian menunjukkan tingkat reaksi peserta memperoleh skor rata-rata 3,37 (84%), dengan aspek pemateri tertinggi. Namun, metode dan jadwal pelatihan masih perlu disempurnakan. Pada tingkat pembelajaran, skor N-Gain sebesar menunjukkan efektivitas sedang. Faktor yang mempengaruhi efektivitas pelatihan meliputi desain pembelajaran, relevansi materi, dan keterbatasan interaksi virtual. Kesimpulannya, pelatihan online ini memiliki potensi meningkatkan kompetensi guru tetapi perlu pendekatan yang lebih inovatif. Rekomendasi mencakup penerapan blended learning, perbaikan metode interaksi, serta strategi interaksi yang lebih efektif. Kata Kunci: kompetensi pedagogi; model Kirkpatrick; pelatihan guru; pendidikan Islam